Cleavages and Electoral Support to Islamist Party in Javan Urban Areas: The Case of Prosperous Justice Party - Alamsyah, Andi Rahman (UI Scholars Hub, 2021)
Several studies have noted that electoral support for one of the Islamist parties in Indonesia, the Prosperous Justice Party (PKS), is mostly concentrated in urban areas. While I agree with this observation, I found that these studies did not pay adequate attention to the diversity of socio-political conditions in urban areas that contributed to the varying electoral support for PKS. One of these socio-political conditions is what Lipset and Rokkan (1967) conceptualized as cleavages (divisions of society). Based on the results of 2014 and 2019 local parliamentary elections in Javan urban areas, I argue that there are three cleavage patterns formed in these areas, namely single dominant, dyadic dominant, and fragmented. Each cleavage pattern has implications for the formation of a type of support for PKS. In regions with single dominant and dyadic dominant cleavages, the Islamist party tends to receive moderate or low support. Further, compared to the the support gained by the winning party, PKS’ votes tends to be much lower. However, in areas with fragmented cleavage, PKS tends to receive high or moderate support, and the votes gained by PKS tend to be comparable to that of the winning party. The data in this article were obtained from secondary data regarding PKS’ gains in the legislative elections for district/city parliaments in 2014 and 2019 in 46 urban areas in Java, online interviews, and literature studies.